The Medan City Drainage Development Policy Review of Al-Maqashid Sharia Theory - Maulana, Riski; Suparmin, Sudirman (Law Development Journal, 2023)
Policy is something that is urgent as a determinant of whether or not the impact will be caused. So that in making a policy, in-depth analysis is needed and attention to various aspects that will intersect with the policy. The drainage development policy in Medan city has raised many questions and complaints from the people directly affected by this development policy. In fact, a policy taken by the government should be able to bring benefits as intended by Maqashid Sharia theory. This research aims to analyse the implementation of the drainage system development policy in Medan city as an effort of flood mitigation program in Medan city area, using Maqashid Sharia theory in order to see the aspect of benefit or even harm caused by the existing policy. This research is a juridical-emperical research by using the concept of statue approach and case approach, this research also uses triangulation technique in analysing the existing data. The conclusion that can be drawn from this research is that there are still many things that must be considered in the process of developing the drainage system in Medan City. When viewed from the perspective of Maqashid Sharia theory, the Medan city government, in this case, which has full authority over the drainage development policy in Medan city, still overrides many aspects. Starting from Hifzh an-Nafs and Hifz al-Mal as a form of safeguarding the rights that should be owned by the community and the public in general.